The use of educational technology in the light of international standards as a reference to measure the effectiveness of using the educational process = استخدام تكنولوجيا التعليم في ضوء المعايير الدولية بوصفها مرجعية لقياس فاعلية الاستخدام في العملية التعليمية - Albusaidi, Faisal Ali Nasser Albusaidi; Sahrir, Muhammad Sabri (OCERINT International, 2020)
This descriptive, analytical study reviews the most important aspects related to measuring the effectiveness of the educational technology used based on international standards for using educational technology, as one of the important benchmarks for building on its educational dimensions and measuring the effectiveness of the use of educational technology. The problem lies in the lack of national standards that can be relied upon in many educational systems in educational institutions to measure the effectiveness of the use of educational technology, as well as the lack of adoption of building national standards on which to base the empowerment of education personnel in the use of educational technology. The study aims to introduce the dimensions of educational technology, its role in the teaching and learning process, and to define international standards for the use of educational technology related to teachers, students or educational leaders. Through the descriptive analytical approach, the study reached several results, the most important of which are: the components of educational technology greatly influence the improvement of the educational process and raise the level of quality in achieving educational goals. Information and communication in education. **************************************************************************** تستعرض هذه الدراسة الوصفية التحليلية أهم الجوانب المتصلة بقياس فاعلية استخدام تكنولوجيا التعليم المستندة إلى المعايير الدولية لاستخدام تكنولوجيا التعليم، بوصفها أحد المحكات المرجعية المهمة التي يمكن البناء على أبعادها التربوية وقياس مدى فاعلية استخدام تكنولوجيا التعليم. تكمن المشكلة في عدم وجود معايير وطنية يمكن الاستناد عليها في العديد من النظم التعليمية بمؤسسات التعليم لقياس فاعلية استخدام تكنولوجيا التعليم، وكذلك عدم تبني بناء معايير وطنية يستند إليها في تمكين قدرات العاملين في التعليم في مجال استخدام تكنولوجيا التعليم. تهدف الدراسة التعريف بأبعاد تكنولوجيا التعليم، ودورها في عمليتي التعليم والتعلم، والتعريف بالمعايير الدولية لاستخدام تكنولوجيا التعليم المتصلة بالمعلمين أو الطلبة أو القادة التربويين. ومن خلال المنهج الوصفي التحليلي توصلت الدراسة إلى نتائج عدة من أبرزها: تؤثر مكونات تكنولوجيا التعليم بصورة كبيرة في تجويد العملية التعليمية، ورفع مستوى جودة تحقيق أهداف التعليم، تعد المعايير الدولية لاستخدام تكنولوجيا التعليم أحدى المحكات المرجعية التي يمكن الاستناد إليها في بناء المعايير الوطنية لاستخدام تكنولوجيا المعلومات والاتصالات في التعليم